Latin America : Vulnerabilities Under Construction? - Cubeddu, Luis.; Tovar Mora, Camilo; Tsounta, Evridiki (Washington, D.C. : International Monetary Fund, 2012)
This paper documents developments in mortgage credit and the housing sector in Latin America over the past decade, and compares them with those of other emerging economies. In particular, it examines the real estate and mortgage markets to assess whether (i) growth in mortgage credit is excessive compared to long-term trends; (ii) trends in house prices reflect changes in economic fundamentals; and (iii) the extent to which household and banking sector vulnerabilities could lead to potential fragilities. Although data limitations hamper a rigorous analysis of trends, our analysis suggests that while there are no imminent misalignments in the real estate and mortgage sectors, they could emerge if current trends persist. Strengthening supervision and addressing data gaps is thus critical to ensure adequate monitoring of risks and vulnerabilities in these sectors.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet